2008
DOI: 10.1038/jid.2008.150
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin3A Alleviates Skin Lesions and Scratching Behavior in NC/Nga Mice, an Atopic Dermatitis Model

Abstract: Topical steroids and antihistamines are commonly used for the treatment of atopic dermatitis (AD). However, in a substantial number of patients with AD, these treatments are not sufficiently effective. In AD patients, C-fibers in the epidermis increase and sprout, inducing hypersensitivity, which is considered to aggravate the disease. Semaphorin3A (Sema3A), an axon guidance molecule, is a potent inhibitor of neurite outgrowth of sensory neurons. To investigate the effect of Sema3A on AD, we administered recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 44 publications
1
69
0
2
Order By: Relevance
“…55) Moreover, histological analyses showed decreases in (i) the numbers of epidermal nerve fibers; (ii) the numbers of inflammatory infiltrates; (iii) the production of cytokines; (iv) the density of dermal blood vessels; and (v) epidermal thickness in Sema3A-treated lesional skin. 54,55) these findings suggest that exogenous Sema3A not only affects sensory nerve fibers, but other cells that express neuropilin-1, include immune system cells, endothelial cells and keratinocytes. 56) Thus, Sema3A and its receptors are promising therapeutic targets for atopic dermatitis.…”
Section: Sema3amentioning
confidence: 94%
See 1 more Smart Citation
“…55) Moreover, histological analyses showed decreases in (i) the numbers of epidermal nerve fibers; (ii) the numbers of inflammatory infiltrates; (iii) the production of cytokines; (iv) the density of dermal blood vessels; and (v) epidermal thickness in Sema3A-treated lesional skin. 54,55) these findings suggest that exogenous Sema3A not only affects sensory nerve fibers, but other cells that express neuropilin-1, include immune system cells, endothelial cells and keratinocytes. 56) Thus, Sema3A and its receptors are promising therapeutic targets for atopic dermatitis.…”
Section: Sema3amentioning
confidence: 94%
“…54,55) the therapeutic efficacy of exogenous Sema3A on atopic dermatitis-like symptoms was greater than that of current agents, such as betamethasone and tacrolimus. 55) Moreover, histological analyses showed decreases in (i) the numbers of epidermal nerve fibers; (ii) the numbers of inflammatory infiltrates; (iii) the production of cytokines; (iv) the density of dermal blood vessels; and (v) epidermal thickness in Sema3A-treated lesional skin.…”
Section: Sema3amentioning
confidence: 97%
“…We have reported that subcutaneous administration of Sema3A ameliorates scratching behavior and skin lesions in the mouse model of atopic dermatitis, suggesting that Sema3A suppresses hypersensitivity to itch by interrupting elongation of peripheral sensory nerve fibers in the epidermis. These results suggest a potential clinical application for Sema3A (24).…”
Section: Introductionmentioning
confidence: 66%
“…These findings may also provide new potential therapeutic targets for ameliorating pruritus associated with epidermal nerve density, including AD. The role of Sema3A in abnormal itch perception has been confirmed by recombinant Sema3A replacement approaches in atopic NC/Nga mice (Yamaguchi et al, 2008). Fig.…”
Section: Wwwintechopencommentioning
confidence: 75%
“…Although the signaling pathways that mediate the regulation of expression of these axonal guidance molecules remain unknown, these findings suggest that abnormal Sema3A and NGF levels in atopic skin are normalized by PUVA therapy, resulting in decreased epidermal nerve density. These PUVA-induced changes in epidermal innervation also have antipruritic effects, as shown by the use of anti-NGF or recombinant Sema3A replacement approaches against pruritus in atopic NC/Nga mice (Takano et al, 2005;Takano et al, 2007;Yamaguchi et al, 2008). Although the mechanisms by which PUVA influences expression of axonal guidance molecules remain unknown, treatment may affect chromatin remodeling and various transcription factors, such as activator protein-1 (AP-1) and poly(C) binding protein (Borner et al, 2002;Kim et al, 2004;Kim et al, 2005;Park et al, 2005).…”
Section: Uv-based Therapy Of Ad Pruritus Involving Epidermal Hyperinnmentioning
confidence: 99%